CIDADANIA PARA TODOS - Ramos, Lizelia T.; Brandão, Emmanuel G. B.; Blaszak, Ediles A.; Beber, Tobias C.; Júnior, Mário d. O.; Bohrer, Luciana; Prestes, Luana M.; Hagemann, Fernanda; Zanella, Giorgia L.; Zeni, Bruna S.; Thomaz, Cesar; Brandt, Daniel; et al. (Salão do Conhecimento, 2013)
Resumo